Biodiversity & environmental management - Joshi, B.D.; Tripathi, C.P.M.; Joshi, P.C.; National Seminar of Indian Academy of Environmental Sciences 2007 : University of Gorakhpur, India) (New Delhi : APH Publishing corporation, 2009)
Papers presented at the 14th National Seminar of Indian Academy of Environmental Sciences, held at Department of Zoology, University of Gorakhpur, November 2007
Keywords: Biodiversity conservation -- India -- Congresses; Environmental management -- India -- Congresses